Epidemiology and Genotypic Diversity of Eurasian Avian-Like H1N1 Swine Influenza Viruses in China - Feng, Zhaomin (Virol Sin, 2020)
Eurasian avian-like H1N1 (EA H1N1) swine influenza virus (SIV) outside European countries was first detected in Hong Kong Special Administrative Region (Hong Kong, SAR) of China in 2001. Afterwards, EA H1N1 SIVs have become predominant in pig population in this country. However, the epidemiology and genotypic diversity of EA H1N1 SIVs in China are still unknown. Here, we collected the EA H1N1 SIVs sequences from China between 2001 and 2018 and analyzed the epidemic and phylogenic features, and key molecular markers of these EA H1N1 SIVs. Our results showed that EA H1N1 SIVs distributed in nineteen provinces/municipalities of China. After a long-time evolution and transmission, EA H1N1 SIVs were continuously reassorted with other co-circulated influenza viruses, including 2009 pandemic H1N1 (A(H1N1)pdm09), and triple reassortment H1N2 (TR H1N2) influenza viruses, generated 11 genotypes. Genotype 3 and 5, both of which were the reassortments among EA H1N1, A(H1N1)pdm09 and TR H1N2 viruses with different origins of M genes, have become predominant in pig population. Furthermore, key molecular signatures were identified in EA H1N1 SIVs. Our study has drawn a genotypic diversity image of EA H1N1 viruses, and could help to evaluate the potential risk of EA H1N1 for pandemic preparedness and response. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12250-020-00257-8) contains supplementary material, which is available to authorized users.